The Effects Of Bank Funds Sources On Bank Profitability In Indonesian Stock Exchange - Magdalena, Annaria; Marpaung, Bintang S; M, Indira E (RISET: Jurnal Aplikasi Ekonomi Akuntansi dan Bisnis, 2019)
The purpose of this research is to analyze the effect of bank funding source to bank profitability. Indicators that are used for this research are Capital Adequacy Ratio, loan received, and third-party funds to Profitability. Population that used on this research are a commercial banks that listed on the Indonesian Stock Exchange. The sample that used are four commercial banks are PT. Bank Mandiri (Persero) Tbk, PT. Bank Rakyat Indonesia (Persero) Tbk, PT. Bank Negara Indonesia (Persero) Tbk, dan PT. Bank Central Asia Tbk on period of 2010-2018. Method that used for this research is using multiple regression analysis by hypothesis test which are, T test and F test. The results of partial hypothesis (T Test) shows that Capital Adequacy Ratio and loan that received has a negative significant influence on Profitability. Meanwhile, Third-party funds have a positive significant influence Profitability. From the results of simultaneous hypothesis testing (F Test) shows that Capital Adequacy Ratio, loans received, and Third-party funds have a significant influence to banks profitability on commercial bank that are go public with significance of 0,000. R square value (R2) on this research is 0,517 or 51,7% and the rest is 48,3% affected by other factor that are not research.